A multi-modal volumetric microscope with automated sample handling for surveying microbial life in liquid samples - Kim, Taewoo; Oborny, Nathan; Serabyn, Eugene; Wallace, J. Kent; Liewer, Kurt; Bedrossian, Manuel; Rider, Stephanie; Noell, Aaron; Willis, Peter; Lindensmith, Chris; Nadeau, Jay (Frontiers in Astronomy and Space Sciences, 2022)
In the study of microbial life, microscopy plays a unique role due to its ability to detect ordered structure, motility, and fluorescence signals. As such it has also recently gained attention in the context of searching for extant life on distant Solar System bodies bearing liquid water. In this paper we introduce a multi-modal volumetric microscopy system for potential future spaceflight missions that combines digital holographic microscopy (DHM) and volume fluorescence imager (VFI), which are volumetric imaging methods that provide high-resolution, high-throughput examination of liquid samples. DHM provides information on the absorption, morphology, and motility of imaged objects without requiring the use of contrast agents. On the other hand, VFI based on light field microscopy focuses on the fluorescence signals from the sample to observe specific structures dyed with targeted contrast agents or providing unique autofluorescence signals. We also present an autonomous sample handling and data acquisition system to allow for an autonomous mission to distant planets or moons, or for autonomous use in bodies of water on Earth. The full system, named ELVIS, or Extant Life Volumetric Imaging System, is capable of autonomously surveying a liquid sample to extract morphology, motility, and fluorescence signals of extant microbial life.